Postural balance, muscle strength and functional capacity on the severity level of chronic obstructive pulmonary disease - Sera Kim, Fabiana; Aguilar Zarpellão, Karlla; Marília Tadayeski Peyres,; Marcos Eduardo SCheicher,; Ambrozin, Alexandre Ricardo Pepe (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Background: Chronic obstructive pulmonary disease (COPD) is characterized by persistent and progressive airflow obstruction. It is a lung disease with systemic manifestations, which contributes to an increase in morbidity and mortality in the elderly. The greater the severity of the disease, more muscle loss occurs, especially the quadriceps muscle, leading to decreased resistance to exercise, increased fatigue, and dyspnea to small efforts. The presence of COPD is associated with an increased risk of falls, and patients with COPD have a greater imbalance when compared with subjects of the same age without the disease. To investigate whether the different degrees of severity of COPD interfere in the balance, muscle strength, and functional capacity of the patients. Methods: 25 individuals diagnosed with COPD (COPD-G) and 32 individuals without pulmonary disease (CG - Control Group) were assessed. Both groups were submitted to anamnesis, spirometry, dynamometry, manovacuometry, Incremental Shuttle WaIking Test (ISWT), load testing for one repetition maximum (1RM), balance platform assessment, Stair-Climbing Test (SCT) and 6 Minutes Walk Test (6MWT). The variables obtained were compared using the t-test. For comparison between groups, a one-way ANOVA was used. Results: The comparison between the two groups showed a difference in the result of the ISWT, 6MWT and SCT. When compared between groups in different degrees of severity, there was a difference only in SCT between CG and severe COPD-G. There was no significant difference in strength and postural balance. Conclusion: Cardiorespiratory functional capacity is impaired in individuals with COPD and is more evident in the severe stage of the disease. The balance, the strength of the respiratory muscles, upper and lower limbs are similar in the mild, moderate, and severe stages.